Evaluation of Information Technology Governance at DISKOMINFO Tasikmalaya City Using COBIT 2019 - Rachmasari Biduri, Nadia; Ramdani, Cecep Muhamad Sidik (Deparment Information System, Siliwangi University, 2023)
The Office of Communication and Informatics (DISKOMINFO) is an agency engaged in the fields of communication, informatics, coding and statistics. Based on the results of interviews with the Head of Application and Informatics DISKOMINFO Tasikmalaya City, it is known that there are obstacles related to limited resources. Starting from human resources, equipment, budget, and also other supporting facilities. So that an evaluation of information technology governance is needed to determine the capabilities possessed by the information technology. This study uses the COBIT 2019 framework using the RACI diagram as a mapping reference for observation and questionnaire distribution. The domains used are BAI02 (Managed Requirements Definition), DSS02 (Managed Service Requests and Incidents), and MEA01 (Managed Performance and Conformance Monitoring). The results of this study are to determine the capability level in each domain so that the current conditions of the Tasikmalaya City DISKOMINFO are obtained. After carrying out the analysis, it was found that the service performance from the BAI02 domain was at level 4, the service performance from the DSS02 domain was at level 2, and the service performance from the MEA01 domain was at level 3. The results of this service performance measurement made a recommendation to be implemented to increase the value information technology governance in accordance with the needs of DISKOMINFO Tasikmalaya City. Capability level objectives can be increased by carrying out activities that are not yet optimal by the agency until it reaches the full value for each level.